2020
DOI: 10.18203/2320-6012.ijrms20204237
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of interleukin-17 levels in gingival crevicular fluid from healthy individuals, chronic gingivitis and chronic periodontitis patients using enzyme linked immunosorbent assay

Abstract: Background: Chronic Periodontitis (CP) is an infectious disease resulting in inflammation of supporting tissues of the teeth. A number of pro-inflammatory cytokines are formed against periodontopathogenic microorganisms. Interleukin-17 (IL-17) is a pro-inflammatory cytokine, implicated in numerous inflammatory and autoimmune conditions.Methods: A total of 25 periodontally healthy subjects (Group 1), 25 patients with gingivitis (Group 2) and 25 patients with CP (Group 3) were included for the study based on cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…and Arief et al21 who reported that the clinical parameters (CAL, PPD) were not correlated with serum IL-17A level of CP patients. In contrast to our study, Nainee et al24 demonstrated that Gingival Crevicular fluid (GCF) concentration of IL-17A cytokine was correlated with clinical parameters of chronic periodontitis patients. The local production…”
contrasting
confidence: 99%
“…and Arief et al21 who reported that the clinical parameters (CAL, PPD) were not correlated with serum IL-17A level of CP patients. In contrast to our study, Nainee et al24 demonstrated that Gingival Crevicular fluid (GCF) concentration of IL-17A cytokine was correlated with clinical parameters of chronic periodontitis patients. The local production…”
contrasting
confidence: 99%
“…The oldest study was from 2005 [ 39 ], and the most recent from 2022 [ 28 ]. Five (41.6%) studies were conducted in India [ 28 30 , 35 , 36 ], two (16.6%) studies in Iran [ 31 , 32 ], and other studies (8.3%) in Saudi Arabia [ 33 ], Japan [ 34 ], Egypt [ 37 ], Turkey [ 38 ], and Chile [ 39 ]. In addition, the title and journals of publication are shown (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine (75%) studies collected GCF samples with absorbent paper strips [ 30 35 , 37 – 39 ] and 3 (25%) studies reported GCF collection using volumetric microcapillary pipettes [ 28 , 29 , 36 ]. Among the 12 included studies, 4 (33.3%) used ELISA kits without brand specification [ 30 , 32 – 34 ], two (16.6%) used R&D Systems ELISA kit [ 36 , 39 ], two others (16.6%) used BioSource ELISA kit [ 37 , 38 ], others (8.3%) used RayBiotech [ 28 ], Diaclone [ 29 ], Bender Med Systems [ 31 ] and eBioscience [ 35 ]. Most of the studies (75%) analyzed cytokine IL-17 levels individually [ 28 30 , 32 , 34 , 36 – 39 ], whereas, 2 others (17%) analyzed IL-23 levels [ 33 , 35 ] and only one (8%) analyzed the IL-23/IL-17 axis together [ 31 ] (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation